PENGARUH BUDAYA ORGANISASI TERHADAP MOTIVASI KERJA PENDIDIK TAMAN KANAK-KANAK DI KECAMATAN SAIL KOTA PEKANBARU - Vina Santa Lucia; Ria Novianti; Febrialismanto ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research was to determine how much influence of organizational culture on work motivation kindergarten teachers in District of Sail Pekanbaru City. The research population was all kindergarten teachers on District of Sail is 32 people. The samples used were a whole number of kindergarten teachers in District of Sail. Data collection techniques used, namely through a questionnaire. Based on the research results of regression equation Y = 20.386 + 0.393X. with the coefficient of determination R2 of 0.419 so that it can be concluded that organizational culture significantly influence employee motivation kindergarten teachers. Based on the results of a simple regression analysis, it can be concluded that "there is a positive and significant influence of organizational culture on work motivation of kindergarten teachers in the district of Sail Pekanbaru City”.Keywords: Organizational Culture,The Work Motivation